2004
DOI: 10.1007/bf03246100
|View full text |Cite
|
Sign up to set email alerts
|

Copper/topaquinone-containing amine oxidase from lentil seedlings and bovine plasma: Catalytic mechanism and energetic domains

Abstract: In this review the characteristics of the prosthetic group and the role of copper in amine oxidase purified from lentil seedlings are compared with the corresponding features of the amine oxidase isolated from bovine serum. Although both enzymes contain the same organic cofactor, the 6-hydroxydopa ( 2,4,5-trihydroxyphenethylamine) quinone, the catalytic cycle of lentil seedling amine oxidase operates through a Cu(I)-free-radical intermediate of the cofactor, whereas in bovine serum enzyme the radical form was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Lentil amine oxidase may be a good example of enzyme where the dynamics of the conformational change, within the active site and at the protein surface, are important in catalysis [5]. LSAO does not show any change in its enzymatic activity by 5% TFE indicating that TFE-enhancing rearrangement of the polypeptide subunits does not change the affinity of substrate for the enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lentil amine oxidase may be a good example of enzyme where the dynamics of the conformational change, within the active site and at the protein surface, are important in catalysis [5]. LSAO does not show any change in its enzymatic activity by 5% TFE indicating that TFE-enhancing rearrangement of the polypeptide subunits does not change the affinity of substrate for the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…AOs catalyze the oxidation of amines as follows: In plants, amine oxidases are involved in process of yellowing, senescence, wound response, cell wall biosynthesis, growth factor and alkaloid biosynthesis [3], well studied examples are the enzymes from the pulses pea (Pisum sativum) [4], lentil (Lens esculenta) [5] and Euphorbia latex [6]. Pea seedling amine oxidase (PSAO) is the only plant enzyme so far crystallized [4].…”
Section: Introductionmentioning
confidence: 99%
“…Following our recent studies of the activity, stability, and energetic domains of LSAO and ELAO, 17,18) in this study the electrochemical behavior of redox centers in the active sites of these enzymes on MFE was scrutinized. Based on our knowledge, this received little attention to date.…”
mentioning
confidence: 99%
“…Plant amine oxidases are soluble dimeric enzymes in which each subunit (about 70 kDa) contains one tightly bound Cu (II) and one tyrosine-derived 6-hydroxydopa quinone (TPQ) as cofactors. 1,2) The crystal structure of pea seedling amine oxidase (PSAO) (PDB code 1KSI) is known.…”
mentioning
confidence: 99%
“…Therefore, LSAO may be considered to have three structural domains (D2, D3, and D4) in each subunit of the enzyme. Previous studies showed that LSAO has three energetic domains 2,6) that may belong to the structural domains.…”
mentioning
confidence: 99%